Assessment Kinerja Keuangan dan Tingkat Kesehatan dalam Mendukung Stabilitas Lembaga Keuangan Mikro Syariah - Silviya Maharani; Wartoyo Wartoyo; Nur Eka Setyowati (Fakultas Ekonomi dan Bisni Islam UIN Siber Syekh Nurjati Cirebon, 2026)
This research is based on the background of sharia operations in Cirebon City facing challenges in the form of organizational and management problems, limited capital, and the low quality of human resources, which makes cooperatives less innovative and efficient and has the potential to reduce their image in society. To improve quality and competitiveness, cooperatives need to implement performance measurement using methods such as CAMEL, RGEC, Balanced Scorecard, as well as cooperative health guidelines from the Republic of Indonesia Minister of Cooperatives and UKM Regulation No. 7/Per/Dep.6/IV/2016. This research uses a quantitative and descriptive approach with primary and secondary data, data collection techniques in this research use observation, interviews and documentation, analyzing eight aspects of cooperative assessment, namely capital, quality of productive assets, management, efficiency, liquidity, cooperative identity, and independence and the growth of sharia principles.. The results show that the Harapan Sejahtera Sharia Consumer Cooperative experienced an increase in its score from 76.60 (fairly healthy) in 2022 to 83.75 (healthy) in 2023, while the Alfa Maratus Sholihah Cooperative increased from 71.15 (fairly healthy ) in 2022 to 83.65 in 2023, with an average rating of quite healthy.